Hughes electrical & electronic technology - Hughes, Edward (Pearson Education, 2016)
All engineers need to understand the fundamental principles of electrical and electronic technology. This best-selling text provides a clear and accessible introduction to the area, with balanced coverage of electrical, electronic, and power engineering.